THE IMPLEMENTATION OF TAX-IN-KIND AND GROSS-UP METHOD IN INCOME TAX ARTICLE 21 ON CORPORATE INCOME TAX AT PT MANGGALA ARYA PRATAMA - Dharmawan, Robin; Yuniarwati , Yuniarwati (International Journal of Application on Economics and Business, 2023)
Taxes are levies paid by individuals and companies to the government to fund various public programs and services. "Tax payable" refers to the amount of tax owed by an individual or company under applicable tax laws. An important aspect of financial management is tax planning. Tax planning is a strategy used by individuals and companies to manage their tax obligations efficiently and legally. The research was conducted at PT MAP. The type of research that the author uses in this final work is descriptive research using case study methods and quantitative analysis research techniques. The data used is primary data from PT MAP.The results of the study show that PPh 21 employees who are grossed up, and the use of natural resources in fiscal reconciliation does not need to be corrected fiscally, is able to save less tax payable